The clinical biochemical and hematological profile of scrub typhus meningoencephalitis - Souvik Sarkar; Soumya Sarathi Mondal; Enamul Hossain; Souvik Kumar Das; Rahul Kumar; Sanjay Kumar Mandal (Asian Journal of Medical Sciences, 2023)
Background: Scrub typhus is a zoonotic infectious disease caused by the Gram-negative coccobacillus Orientia tsutsugamushi. Meningoencephalitis occurs in two-thirds of all the infected cases. Aims and Objectives: The study of these cases was conducted to study the clinical, biochemical, and hematological features of scrub typhus meningoencephalitis. Materials and Methods: We included 12 patients who were admitted in the General Medicine Ward of Medical College and Hospital, Kolkata, between May 2021 and July 2022. The serum scrub typhus immunoglobulin M (IgM) test was used to diagnose the cases after ruling out dengue, malaria, leptospirosis, bacterial, tubercular, and viral meningoencephalitis. Results: A triad of fever, altered sensorium, and meningeal signs were present in all of the cases. 2 patients had seizures, 1 patient had lateral rectus palsy, 1 patient had a generalized maculopapular rash, and eschar was seen in only 2 cases. The most common laboratory abnormalities were hyponatremia, anemia, and transaminitis (each 83.33%). 8 cases (66.7%) had a combination of anemia, hyponatremia, and transaminitis. Cerebrospinal fluid abnormalities included protein elevation (75%) and lymphocytic pleocytosis (83.33%). Scrub typhus IgM was positive in all of them. All the cases showed excellent response to doxycycline. Conclusion: A high degree of clinical suspicion is required to diagnose scrub typhus meningoencephalitis. The eschar is detected in very few cases and it may be difficult to recognize the same among the dark-skinned Indian population. However, as per our study, any case of meningoencephalitis with a combination of anemia, hyponatremia, and deranged liver function tests should always raise the possibility of the aforementioned disease and doxycycline therapy must be started promptly.